PTFI Lipidomics of Animal Food (Red method): Standard Operating Procedure (SOP) - Odenkirk, Melanie T (2024)
This Standard Operating Procedure (SOP) describes a shotgun lipidomics method for analyzing 19 lipid classes in animal and animal by-product foods using a shotgun lipidomics method implemented on a Sciex 5500 or 6500 instrument with Selexion Technology. The protocol involves extracting lipids from lyophilized animal materialusing a modified Bligh-Dyer biphasic extraction with DCM/MeOH/water, followed by two acquisition methods to detect phospholipids, glycerolipids, sphingolipids, free fatty acids, and cholesterol esters. Key features include the use of Ultimate Splash One and PTFI Animal Supplement internal standards, DMS tuning optimization with EquiSPLASH, and automated data processing through Shotgun Lipidomics Assistant software, specifically designed for the Periodic Table of Food Initiative to characterize lipid profiles across diverse animal species. For unresolved issues, users are encouraged to seek additional assistance via ptfionboarding@gmail.com.